Corporate social irresponsibility a challenging concept - Tench, Ralph; Sun, William, 1962-; Jones, Brian (Critical studies on corporate responsibility, governance and sustainability, 2012)
Corporate social responsibility (CSR) has become an increasingly heated topic since the 1980s. But there are severe limitations with the concept of CSR and the effectiveness of CSR practices. Addressing such limitations, this volume proposes that the concept of Corporate Social Irresponsibility (CSI) offers a better theoretical platform to avoid the vagueness, ambiguity, arbitrariness and mysticism of CSR. It challenges conventional modes of thinking, unveils the CSR mask of business practices and redirects public attention to the core issues of CSR. This collective work sets up an initial theoretical framework for the subject of CSI and examines the fundamental reasons for irresponsibility in and beyond a corporate context. Rooted in theory and practice it seeks to understand how boundaries of CSR and CSI have been constructed in society, and explores some systemic and structural issues of CSI in practice.